Effect of No-Reflow During Primary Percutaneous Coronary Intervention for Acute Myocardial Infarction on Six-Month Mortality - Muhammad Ijaz Khan, Muhammad Umar Farooq, Hamid Iqbal, Syed Imran Ahmed Kazmi, Iffat Aqeel, Bakht Umar Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: No-reflow is a serious complication that can occur during primary percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI). No-reflow is a frequent event during percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI), and it may affect cardiac prognosis. Objectives: The main objective of the study is to find the effect of no-reflow during primary percutaneous coronary intervention for acute myocardial infarction on six-month mortality. Methods: This study was conducted at Ayub Teaching Hospital Abbottabad over a period of six months (1st January 2022 to 30th June 2022). A total of 130 patients who underwent primary PCI for AMI were included. The occurrence of no-reflow during the procedure was noted, and six-month mortality was recorded. Results: Of the 130 patients included in the study, 34 (26.2%) developed no-reflow during PPCI. The mean age of the patients was 58.5 ± 9.6 years, and 73.8% were male. The most common risk factors for AMI were hypertension (52.3%), smoking (45.4%), and diabetes (36.2%). There were no significant differences in baseline clinical and angiographic characteristics between patients with and without no-reflow. Conclusions: The occurrence of no-reflow during primary PCI for AMI is associated with a higher six-month mortality rate. Further research is needed to explore strategies to prevent or mitigate the occurrence of no-reflow during primary PCI for AMI. Keywords: AMI, No-reflow, Mortality, percutaneous coronary intervention (PCI)